2018
DOI: 10.1177/0034644618770761
|View full text |Cite
|
Sign up to set email alerts
|

Genesis of U.S. Colorism and Skin Tone Stratification: Slavery, Freedom, and Mulatto-Black Occupational Inequality in the Late 19th Century

Abstract: Studies show lighter skinned Black people are advantaged on a number of social indicators—a phenomenon called “colorism.” These studies generally contend preferences for light-skinned and/or Mulatto slaves endured the postbellum period to shape social outcomes into today. Following this idea, other studies examine differences in social outcomes between Mulattos and Blacks in the 19th century, but few empirically connect antebellum life to postbellum Mulatto–Black stratification. With that in mind, I examine wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…Examining whether the racial structure in the United States is more spectral or categorical helps us understand whether color has come to trump race in shaping social outcomes. It is possible in the absence of formal, legal racial barriers to black advancement in the wake of the Civil Rights Act of 1964, lighter skinned black Americans who had enjoyed superior social outcomes since chattel slavery were poised to rapidly increase their social standing in a way that sharply diverged with darker skinned black Americans (Reece 2018). This may suggest our traditional ways of conceptualizing and measuring race and color have become antiquated as legal barriers were dismantled.…”
Section: Color Race and Intersectionalitymentioning
confidence: 99%
“…Examining whether the racial structure in the United States is more spectral or categorical helps us understand whether color has come to trump race in shaping social outcomes. It is possible in the absence of formal, legal racial barriers to black advancement in the wake of the Civil Rights Act of 1964, lighter skinned black Americans who had enjoyed superior social outcomes since chattel slavery were poised to rapidly increase their social standing in a way that sharply diverged with darker skinned black Americans (Reece 2018). This may suggest our traditional ways of conceptualizing and measuring race and color have become antiquated as legal barriers were dismantled.…”
Section: Color Race and Intersectionalitymentioning
confidence: 99%
“…Evidence shows that skin tone’s importance originated during slavery (see Reece 2018), where, as Keith and Herring (1991:2) point out, lighter-skinned Blacks were privileged by whites and thought to be more aesthetically appealing and intellectually superior to darker-skinned Blacks—thinking that typically rested on a foundation of “race science” that held that lighter-skinned Blacks (i.e., those who had kinship ties with whites, hence the lightness of these individuals’ skin tones) were less African and more European and thus superior to other Blacks (Reuter 1918). The adoption of such thinking by whites afforded lighter-skinned Blacks advantages in obtaining education, property, and even their freedom (i.e., manumission).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the findings, a few broad observations can be made. First, major discrimination faced by African Americans from colorism can influence psychological trauma (e.g., Diette et al., 2015; Reece, 2018). It is suggested that colorism impacts have a far‐reaching cost on health and general well‐being (Bertocchi & Dimico, 2014; Blair et al., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Discrimination based on skin color is not just a U.S. problem, but it is a social ill among people of color (Banks, 2015; Hall, 2018; Hunter, 2015; Jayawardene, 2016). However, African Americans have an inimitable experience with colorism because of its roots in slavery (Hill, 2002; Reece, 2018).…”
Section: Introductionmentioning
confidence: 99%